How Do Adolescents Navigate Covid-19 Information, and Why Does It Matter? - Vanegas-Lopez, J; Maddaleno-Herrera, M (INT SOC GLOBAL HEALTH, 2021)
The most reported sources of information about COVID-19 were news reports (government or non government), health professionals, family members, and teachers. However, across sites, there were differences by sex. Girls were more likely to rely on family members and teachers, whereas boys were more likely to rely on reputable health and government organizations. Adolescents determined trustworthiness of the sources using a mental ranking on whether the information was logical and could be cross-verified.